Mastering Media: A Review of Paolo Granata’s MediuM - A Marshall McLuhan Board Game - Maynard, Luke R. J.; Martins, Vanessa; Hawkins, Kathryn (New Explorations, 2023)
The aim of this paper is to review The MediuM, a board game developed by professor Paolo Granata with his students in the Book & Media Studies Program at St. Michael’s College in the University of Toronto. It is based on Marshall McLuhan’s Laws of Media and one of its goals is to stimulate creative and fast thinking skills. After playing the game, we inferred that it encourages players to think about how technology, as McLuhan argued, determines society and, at the same time, how people cannot be functionally separated from them.